The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.48550/arxiv.2112.02035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dephasing-enhanced performance in quasiperiodic thermal machines

Cecilia Chiaracane,
Archak Purkayastha,
Mark T. Mitchison
et al.

Abstract: Understanding and controlling quantum transport in low-dimensional systems is pivotal for heat management at the nanoscale. One promising strategy to obtain the desired transport properties is to engineer particular spectral structures. In this work we are interested in quasiperiodic disorder -incommensurate with the underlying periodicity of the lattice -which induces fractality in the energy spectrum. A well known example is the Fibonacci model which, despite being non-interacting, yields anomalous diffusion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The popular quasi-periodic lattice systems, namely, the Aubry-André-Harper (AAH), its generalised version GAAH model and the Fibonacci model [21,22] have been studied extensively in the context of boundary driven dissipative quantum transport [23][24][25][26][27][28][29]. Further studies have started to emerge to understand the environment induced effects on transport [30][31][32][33][34][35][36][37] in such systems. Very recently, following the local Lindblad master equation formalism, the steady-state transport properties due to dephasing noise were analyzed for AAH and Fibonacci models [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popular quasi-periodic lattice systems, namely, the Aubry-André-Harper (AAH), its generalised version GAAH model and the Fibonacci model [21,22] have been studied extensively in the context of boundary driven dissipative quantum transport [23][24][25][26][27][28][29]. Further studies have started to emerge to understand the environment induced effects on transport [30][31][32][33][34][35][36][37] in such systems. Very recently, following the local Lindblad master equation formalism, the steady-state transport properties due to dephasing noise were analyzed for AAH and Fibonacci models [34].…”
Section: Introductionmentioning
confidence: 99%
“…Following a similar approach, the effect of dephasing noise on transport was studied in presence of mobility edge [35]. Another recent work [36] focused on understanding thermoelectric transport properties for Fibonacci type model using the first principle Büttiker voltage-temperature probe approach, [38][39][40][41] where it was shown that noise induced processes can lead to a better thermoelectric performance in certain regimes of transport. Note that, such a Büttiker probe technique was used extensively in the past to understand effective many-body transport properties in setups like molecular junctions [42][43][44][45][46][47][48][49], quantum dots [50], lattice models of oscillators [51][52][53] etc.…”
Section: Introductionmentioning
confidence: 99%